2012
DOI: 10.3201/eid1806.110139
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant Fecal Carriage of Extended-Spectrum β-Lactamase–producingEnterobacteriaceaeand Infection after Liver Transplant, France

Abstract: Bacterial infection after liver transplant is fairly common, mostly because liver transplant patients are severely ill and the surgery is very complex. Adding to the seriousness of this situation is that some bacteria are resistant to many antimicrobial drugs. However, treating all infections as drug resistant would lead to even more drug resistance, so only patients at highest risk should receive the most powerful drugs. But who is at highest risk? A recent study in France screened fecal samples of liver tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
103
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 34 publications
5
103
0
3
Order By: Relevance
“…Our findings are consistent with those from previous animal (9) and clinical (12) studies. Persistent intestinal colonization by endogenous flora carrying resistance genes would increase the likelihood of the transmission of resistance to the community (42) and of future infection by resistant pathogens (43,44). Clinicians caring for patients who have had recent ICU stays should consider previous colonization by resistant pathogens and their antibiotic resistance spectra.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those from previous animal (9) and clinical (12) studies. Persistent intestinal colonization by endogenous flora carrying resistance genes would increase the likelihood of the transmission of resistance to the community (42) and of future infection by resistant pathogens (43,44). Clinicians caring for patients who have had recent ICU stays should consider previous colonization by resistant pathogens and their antibiotic resistance spectra.…”
Section: Discussionmentioning
confidence: 99%
“…Because we studied commensals, only 8 ESBL isolates were B2, and 3 among them were ST131. This may be seen as a study limitation; however, ESBL E. coli carriage has been shown in several studies to precede infection, and carriage of ESBL E. coli is linked to the risk of ESBL urinary tract infections in women with the same clone of ESBL E. coli found in urine samples as in fecal samples (3,18,19).…”
mentioning
confidence: 97%
“…P1 patients were older than P2 patients (average P1 age, 66.6 years [standard deviation, or SD,18.9] versus 57 years [SD, 16.1] for P2 patients; P Ͻ 0.01); patient characteristics were otherwise similar in both periods. Table 1 represents the characteristics of ESBL E. coli strains carried in P1 and P2 patients.…”
mentioning
confidence: 99%
“…A few studies have related resistance, using treatment resistance breakpoints; to post-operative infection (14)(15)(16)(17)(18)(19). The main area this has been investigated is liver transplantation, it is assumed this relates to the potentially high mortality rate associated with post-operative infections.…”
Section: Clinical Studies Into Antibiotic Resistance and Surgical Promentioning
confidence: 99%
“…The main area this has been investigated is liver transplantation, it is assumed this relates to the potentially high mortality rate associated with post-operative infections. The most informative study, by Bert et al, showed that pre-operative colonisation with ESBL Enterobacteriaceae increased the rate of post operative ESBL infections, although the overall infection rate was not reported (14). Within surgical biopsies of the prostate, another situation where prophylaxis is used, colonisation with ciprofloxacin resistant Enterobacteriaceae has been shown to indicate a higher risk of post-operative infection, 7.1% vs. 1.1%, in those not colonised (17).…”
Section: Clinical Studies Into Antibiotic Resistance and Surgical Promentioning
confidence: 99%